2011
DOI: 10.1111/j.1467-7717.2011.01267.x
|View full text |Cite
|
Sign up to set email alerts
|

Disaster risk reduction capacity assessment for precarious settlements in Guatemala City

Abstract: This study presents findings of an institutional capacity analysis of urban disaster risk reduction for informal settlements in the Guatemala Metropolitan Region. It uses a resource access perspective of vulnerability, actor-network theory, and qualitative data collection. The analysis reveals that there is interest in disaster risk reduction for the informal settlements; however, there is little in the way of direct financial or oversight relationships between informal settlement residents and all other actor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Most people in informal settlements are migrants from rural villages who simply do not have the means to afford better housing on their own. Previous studies have also shown that during recovery phase, residents will often not wait for city plans to start the reconstruction phase and will reconstruct basing on their capabilities, without regard to resilience (Oliver-smith and Goldman, 1988;Wamsler, 2004;Miles et al, 2012). The evidence from Mzuzu also confirms the observation by Wamsler (2004) that those reconstructing after a disaster sometimes build in the same risky areas.…”
Section: Are There Alternatives?supporting
confidence: 62%
See 1 more Smart Citation
“…Most people in informal settlements are migrants from rural villages who simply do not have the means to afford better housing on their own. Previous studies have also shown that during recovery phase, residents will often not wait for city plans to start the reconstruction phase and will reconstruct basing on their capabilities, without regard to resilience (Oliver-smith and Goldman, 1988;Wamsler, 2004;Miles et al, 2012). The evidence from Mzuzu also confirms the observation by Wamsler (2004) that those reconstructing after a disaster sometimes build in the same risky areas.…”
Section: Are There Alternatives?supporting
confidence: 62%
“…Prohibitive land markets and high levels of poverty force large numbers of rural-urban migrants to occupy informal settlements, which are often the only places they can afford (Miles et al, 2012;Isunju et al, 2016). Most informal settlements are located in areas prone to multiple hazards, often in land that is ignored by the rich because of its susceptibility to disasters such as floods, earthquakes, landslides and fire (Tipple, 2006;Bull-Kamanga et al, 2003;Moser, et al, 2010;Baker, 2012;Usamah et al, 2013;Castro et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Returning population to communities affected by disturbances has been used to indicate social recovery (Aldrich 2012; Chang 2010; Finch et al 2010; Li et al 2010). The four categories of recovery are related, for example, with repair to infrastructure being necessary to support returning population and businesses (Miles et al 2012), and the recovery of social systems encouraging the rebuilding of infrastructure components (Tierney and Oliver-Smith 2012). Hence, the recovery indicator could be a combination of variables from different dimensions.…”
Section: Methodsmentioning
confidence: 99%
“…Informal settlements are often perceived as or placed outside the law (Larson, 2002). Second, resilience initiatives in precarious settlements are likely to be defined by a poorly coordinated mix of organisations and agencies that are detached from the affected communities, with NGOs playing a prominent role (MacKinnon and Derickson, 2012;Miles, Green, and Svekla, 2012). Indeed, 'NGOisation'-the embeddedness of NGOs in national governance structures and the co-optation of civil society organising under issue-specific NGOs-has been on the rise (Hearn, 1998;Stubbs, 2007;Choudry, 2010).…”
Section: The 'Robust City' Strand Of the Urban Resilience Discoursementioning
confidence: 99%